Potential Detection of Secular Evolution of Chemical Abundances on the Surface of the HgMn Primary in the Triple System χ Lup - Järvinen, Silva (2020)
Se dectriben las detecciones en: HgMn Primary in the Triple System χ Lup realizadas con instrumentos del CASLEO.